Analysis Of Challenges and Potentials in Improving Quality of Education for Village Communities - Sonia Sonia; Salahudin Salahudin (Budapest International Research and Critics University, 2022)
This study aims to analyze and describe various challenges and potentials in Quality Village Education. The main purpose of education is to improve the quality of human resources (Human Resources). Education functions as a process by which a person is educated to have moral qualities and skills that will later be useful for the progress of this country. Education is a bridge for someone to be able to enter the world of work. Therefore, quality education is needed to increase a person's potential in order to enter the world of work in accordance with his wishes. However, education in Indonesia today does not reflect the function and purpose of actual education. The quality of education in this country must be further improved because if you want to create quality human beings and create a prosperous and prosperous village, then education itself must also be improved in order to create a prosperous and quality education. The research method applied in this research is the research method. qualitative analysis of content regarding Quality Village Education. Big Data analysis using Nvivo 12 plus analysis software. The results of this study contribute to the formulation and development of Village SGDs, especially regarding the challenges and potentials of quality village education. secondary data, namely SDGs documents and journals related to Quality Village Education. The next research needs to use secondary data.